2015
DOI: 10.1371/journal.pone.0117223
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Improves 3-NPA-Induced Memory Impairment in Ovariectomized Rats: Impact of Its Antioxidant, Anti-Inflammatory and Acetylcholinesterase Modulatory Properties

Abstract: Huntington’s disease (HD) is a progressive neurodegenerative disorder. The pre-motor symptomatic stages of the disease are commonly characterized by cognitive problems including memory loss. 3-Nitropropionic acid (3-NPA) is a mitochondrial toxin that produces selective lesions in the brain similar to that of HD and was proven to cause memory impairment in rodents. Phytoestrogens have well-established neuroprotective and memory enhancing effects with fewer side effects in comparison to estrogens. This study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 78 publications
1
43
0
1
Order By: Relevance
“…Accumulating evidence has shown that phytoestrogens exert beneficial effects in a variety of neurodegenerative disorders, including acute ischemic stroke [8-10] Due to a structural similarity to the mammalian estrogen, phytoestrogens can selectively bind estrogen receptors (ERs) to regulate relevant gene expression and produce estrogenic and/or anti-estrogenic effects. Calycosin, as an isoflavone phytoestrogen isolated from Astragalus membranaceus , is found to possess various potential pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that phytoestrogens exert beneficial effects in a variety of neurodegenerative disorders, including acute ischemic stroke [8-10] Due to a structural similarity to the mammalian estrogen, phytoestrogens can selectively bind estrogen receptors (ERs) to regulate relevant gene expression and produce estrogenic and/or anti-estrogenic effects. Calycosin, as an isoflavone phytoestrogen isolated from Astragalus membranaceus , is found to possess various potential pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The emission spectrum of the BSA overlaps with the absorption spectrum of these compounds, as shown in Figure 5. According to equations (6)(7)(8), the values of E, J (λ), R 0 and r 0 can be calculated, which are listed in Table 4. The values of r 0 were 2.56, 1.81, 2.65, 2.64, 2.69 nm for GEN, GEN1, GEN2, GEN3 and GEN4, respectively, which were all much smaller than the academic value (7 nm).…”
Section: Energy Transfer From Bsa To Five Compoundsmentioning
confidence: 99%
“…Genistein, a major isoflavone in soybean, possesses many biological and pharmacological activities including estrogenic, antioxidant, anti‐inflammatory and antibacterial properties, anticancer activity . However, the clinical use of genistein is limited due to its poor water solubility and low bioavailability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genistein (5,7,4’‐trihydroxyisoflavone), mainly found in legumes, displays antitumor, anti‐inflammatory, antioxidant, anti‐osteoporotic, antimicrobial properties and its antitumor activity has always been the focus of research. Although genistein possesses various biological activities, its poor solubility and low bioavailability limited its potential in clinical treatment , .…”
Section: Introductionmentioning
confidence: 99%